Measuring the Electability of Gibran Rakabuming in the Vortex of Political Dynasty among Gen-Z in Surakarta - Hudha, Bahtiar Nurul; Putri, Febriana Andiani; Rezky, Aulia Putri (Publik : (Jurnal Ilmu Administrasi), 2023)
The purpose of this study is to analyze the electability of Gibran Rakabuming in facing the 2024 general election contestation among Gen-Z amid the issue of dynastic politics. Gibran has become a topic of conversation because of the controversy over the issue of his rise as a vice presidential candidate, which is allegedly strong with the influence of the family, namely Jokowi as president. In addition, the issue of young people is the context that Gibran always expresses to get public votes. To analyze this issue, the researchers uses descriptive quantitative research methods by distributing questionnaires to 100 respondents. The criteria for these respondents are residents of Surakarta City and young people with an age range of 17-26 years. In addition, this research also uses Nvivo 12 plus tools to find out Gen-Z's views on Gibran's performance as Mayor of Surakarta. The results of this study reveal that the majority of Gen-Z disagree with the existence of dynastic politics and strongly support leaders who came from young people. Gen-Z is satisfied with the results of Gibran's performance as Mayor of Surakarta but tends to disagree with Gibran's decision to become Vice President. This study found that 50% of Gen-Z were neutral or hesitant to vote for Gibran as vice president, 30% did not vote for Gibran and 20% voted for Gibran. This hesitation is mostly because Gen-Z cconsiders that Gibran does not have much experience in politics.